Ordenamiento de las comunidades vegetales herbáceas del departamento Rosario (Prov. Santa Fe, Argentina) - Collantes, Marta Beatríz; Lewis, Juan Pablo (Ecosur, 2023)
The data collected from some herbaceus communities of the Department of Rosario which were already published in a previous paper, have been analyzed by a more objective ordination method; correspondence analysis (or reciprocal averaging). The latter ordained the “relevés” along two gradiente which were correlated with the topography of the sampled area. The major gradient was associated to soil salinity, whereas the secondary one corresponded with soil moisture. It is shown that the classical phytosociological analysis, although subjective, yields sound and reproducible resulte.